Analisis Bibliometrik Trend Penelitian Komunikasi Krisis Public Relations di Indonesia: Bibliometric Analysis of Public Relations Crisis Communication Research in Indonesia - Astuti, Vivien Febri; Wijaya, Abung Supama; Suwanda, Bayu Suriaatmaja; Willy Bachtiar (IPB University, 2023)
This research aims to analyze the development of research on crisis communication in public relations, classify it based on trends, and identify potential variables for future research. This study uses a literature review method or bibliometric analysis approachThe research started with defining the keywords